An Adaptive PID Load Frequency Control of Islanded Microgrids Based on Iterative Learning Control - Rehiara, Adelhard Beni; Sarungallo, Pandung; Rumengan, Yanty; Lesnussa, Henny A. B.; Patiran, Abdul Zaid (International Journal of Integrated Engineering, 2025)
The deviation in frequency could be a major issue in power system operation because it can affect the stability of the system. Load frequency control (LFC) is needed to control the deviation so that system stability can be maintained. The LFC is often referred to as automatic generator control (AGC) microgrids in islanded mode. In this paper, an adaptive PID control based on iterative learning control (ILC) is proposed to handle power system dynamics on an islanded microgrid. The results show that the proposed PID controller has better performance under various disturbances, such as load changes and penetration of external generation, such as wind power, while adhering to the 2% overshoot and 2% steady state band constraints. During simulation, the proposed controller has demonstrated its superiority over the classical PID tuning.